Developing Students’ Communicative Competence in the Framework of the Competence-Based Approach - Davronova Nilufar Baxtiyor qizi (International Journal on Integrated Education, 2022)
The article describes issues based on developing students’ communicative competence in the framework of the competence-based approach. The main goal of learning a foreign language is communicative competence. Communication, communication lies at the basis of all human activity, is an incentive for action, the basis of our judgments and ideas about the world, contributes to the effective interaction of people. As well as, in the context of teaching foreign languages, we should talk about the dialogue of cultures and intercultural communication, where the communication process becomes more complicated, since the participants may have different views of the world, which leads to a misunderstanding of information.